Inflammatory osteolysis: a conspiracy against bone - Mbalaviele, Gabriel; Novack, Deborah V.; Schett, Georg; Teitelbaum, Steven L. (Journal of Clinical Investigation, 2017)
There are many causes of inflammatory osteolysis, but regardless of etiology and cellular contexts, the osteoclast is the bone-degrading cell. Thus, the impact of inflammatory cytokines on osteoclast formation and function was among the most important discoveries advancing the treatment of focal osteolysis, leading to development of therapeutic agents that either directly block the bone-resorptive cell or do so indirectly via cytokine arrest. Despite these advances, a substantial number of patients with inflammatory arthritis remain resistant to current therapies, and even effective anti-inflammatory drugs frequently do not repair damaged bone. Thus, insights into events such as those impacted by inflammasomes, which signal through cytokine-dependent and -independent mechanisms, are needed to optimize treatment of inflammatory osteolysis.
EVALuna2:13420